The fire witness - Kepler, Lars (Kepler, Lars. Joona Linna novel., 2013)
When a medium contacts the police department with claims about a murder at a rural home for wayward girls, detective Joona Linna investigates bizarre clues only to find himself confronting more violent truths and a figure from his past.